Complete Genome Sequence of a Novel Azospirillum Strain TA Isolated from Western Siberia Chernevaya Taiga Soil - Mikhail Rayko; Irina Kravchenko; Alla Lapidus (Microorganisms, 2024)
A whole genome sequence of a new strain of the nitrogen-fixing bacterium Azospirillum doebereinerae, known for its diverse plant growth-promoting bacteria (PGPB), was obtained for the first time. The strain, designated Azospirillum doebereinerae AT, was isolated during a soil analysis in the Chernevaya taiga of Western Siberia, a unique and fertile forest ecosystem known for its diverse plant growth-promoting bacteria (PGPB). The A. doebereinerae genome under study is fully assembled into seven circular molecules, none of which are unequivocally plasmids, with a total length of 6.94 Mb and a G + C content of 68.66%. A detailed phylogenomic analysis confirmed its placement within the genus Azospirillum, specifically closely related to A. doebereinerae GSF71T. Functional annotation revealed genes involved in nitrogen metabolism, highlighting the potential of strain TA as a biofertilizer and plant growth-promoting agent. The findings contribute to our understanding of the genomic diversity and metabolic potential of the Azospirillum genus, and they are of interest for further study in the field of comparative bacterial genomics, given the strain’s multi-chromosomal genome structure.